Enhanced anti-bacterial activities of ZnO nanoparticles and ZnO/CuO nanocomposites synthesized using Vaccinium arctostaphylos L. fruit extract. (31st October 2018) - Mohammadi-Aloucheh, Ramin; Habibi-Yangjeh, Aziz; Bayrami, Abolfazl; Latifi-Navid, Saeid; Asadi, Asadollah
Abstract: A green synthesis route was developed for preparation of the ZnO nanoparticles and ZnO/CuO nanocomposites by using Vaccinium arctostaphylos L. fruit extract, and their anti-bacterial activities against two pathogenic bacteria, Escherichia coli (Gram negative) and Staphylococcus aureus (Gram positive), were investigated. The fabricated nanomaterials were characterized by XRD, EDX, FESEM, TEM, TGA, FT-IR, UV–vis DRS and BET instruments. The results showed that the sizes of ZnO and CuO nanoparticles in the ZnO/CuO (10%) nanocomposite were 12 and 8 nm, respectively. In addition, specific surface areas of the ZnO (W), ZnO (ext) and ZnO/CuO samples were 29.3, 27.5 and 18.0 m 2 /g −1, respectively. The results obtained from EDX, TGA, FT-IR and UV–Vis DRS analyses displayed that some of the organic compounds from the fruit extract have bonded to the surface of the samples fabricated in the presence of the fruit extract. The results revealed that the anti-bacterial activity of the fabricated samples is as ZnO/CuO (10%) > ZnO/CuO (5%) > ZnO (ext) > ZnO (W). Viability percentages for E. coli and S. aureus bacteria were 12.1 ± 0.39 and 14.9 ± 0.65 in the presence of the ZnO/CuO (10%) nanocomposite, respectively. The SEM images clearly demonstrated the disruption of the bacterial membranes during the inactivation process. Graphical Abstract: UF0001